An indirect measure (time estimation) as a prediction of typing skill : a thesis ... for the degree of Master of Arts in Applied Psychology at Massey University - Johnson, Irene (Massey University, 1979)
This study investigates the possibility of predicting performance on a complex skill (typing), with an indirect test (time estimation on a card-sorting task). It was hypothesised that typing skill could be predicted from the time subjects estimated they took to perform the card sorting task; independently of the actual time they took to do the task or their achievement motivation. The various methods of personnel selection are reviewed, as well as the factors influencing time perception. Sixty adolescents and forty-two adults in beginners' typing classes were administered the time estimation task and an achievement motivation questionnaire. Their typing performance was tested after eight months. The results did not confirm the hypothesis. No significant relationship was found between time estimation and subsequent typing performance; while achievement motivation was significantly correlated with typing performance.
Keywords: Typewriting